Detection of a glass fiber-reinforced polymer with defects by terahertz computed tomography - Qing Yang Steve Wu; Nan Zhang; Vincent Lim; Lei Zhang; Yu Zhong; Benjamin Russell; Lin Ke (ChemPhysMater, 2024)
Terahertz (THz) computed tomography (THz CT) exhibits the potential to provide a wealth of data, surpassing that of THz tomographic imaging in applications such as detecting embedded defects, particularly defect evolution within a glass fiber-reinforced polymer. To realize high-resolution THz CT, a systematic approach guided by wave propagation simulation was employed. First, the front wave of the THz beam was fine-tuned to realize a beam diameter of <2 mm. To mitigate the strong refractive effect and minimize Fresnel reflection loss, a refractive-index-matching material was fabricated and utilized as a rounded enclosure for samples with sharp corners. To further improve the reconstruction resolution, a flat surface enclosure was applied to collect all incident beams at the detector. To realize comparable results to those of full-angle CT, a limited-angle CT approach was implemented, and the frequency range 0.1–3 THz was used in the image reconstruction study. The experimental and simulated images were used to validate the findings, and conductive and non-conductive defects measuring 200 µm were successfully visualized. Additionally, a custom-built user interface enabled us to visualize the field spatial distribution of the THz beam with respect to frequency.